Could Nightingale get cancelled? The rise, endurance, and possible fall of Florence Nightingale in British historical culture since 1854. Issue 7 (10th November 2022) - Bates, Richard; Greenwood, Anna
ABSTRACT : Since she exploded into the public sphere in 1854 with her mission to the Crimean War, Florence Nightingale (1820-1910) has been a revered historical heroine, with a presence in British commemorative culture that exceeds that of any other non-royal woman. This article, for the first time, delineates and analyses the contours and contents of the commemorative culture around Nightingale, examining how these have changed since the 1850s. It is, we argue, the way the Nightingale story spoke to various (changing) contemporaneous contexts in the spheres of femininity, humanitarianism, Christianity, and nursing which account for the way she was rarefied, and endured, as a female national icon. We then move on to describe the ways, since 1918, Nightingale's reputation has increasingly been subject to criticism. This iconoclasm reached its apotheosis from the 1980s onwards, when Mary Seacole emerged as a rival for the public commemoration of nurses. We raise the possibility that –particularly in the context of Black Lives Matter and increased questioning of the celebration of individuals who operated from places of privilege and power—our current cultural moment may mark, if not the end of public enthusiasm for Nightingale, a fragmentation of her memory along political lines.